International Financial Statistics, June 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This June 2015 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. IFS publish, for most countries of the world, current data on exchange rates, international liquidity, international banking, money and banking, interest rates, prices, production, international transactions (including balance of payments and international investment position), government finance, and national accounts. Information is presented in tables for specific countries and in tables for area and world aggregates. IFS is published monthly and annually. In IFS, exchange rates are expressed in time series of national currency units per SDR (the unit of account for the IMF) and national currency units per US dollar, or vice versa.